The Hospital Problem : the Report of a Special Conference of Labour, Hospital, Medical and kindred Societies (London : The Labour Party ; printed at the Office of the British Medical Association, 1924)
1924 1924 1920s 12 pages 5 let the letters "C.O.S." stand for "Choke off sympathy," for they had nothing to do with charity. Where had the standard for the sick poor been kept up except at the voluntary hospitals? Where had preventive medicine been developed? Voluntary hospitals, of course, had not done all that they wanted to do. They had not beds enough. Sometimes also they were too much dependent on amiable fanatics! But if the voluntary hospitals were good, let them be strengthened, not thrown over. He could not pass by in silence the catalogue of abuses which the Labour party had set out in this pamphlet. He had never seen anything better written, and yet it was full of misstatements likely to cause pain. It was said that the hospitals were badly understaffed. As regards in-patients this was absolutely untrue; as regards out-patients it was half true. It was said that only men with money could get on the staff because only they could afford to wait. That was untrue. No man fit to be on the staff of the London Hospital and who was known to be likely to be a valuable member had ever failed to get on it during his experience of the hospital. With regard to nurses, in some hospitals, though certainly not at the London, nurses were underpaid, but that was no reason for condemning the voluntary hospitals. He denied the statements with regard to the conditions under which nurses worked. He did not believe that nursing could be said to be an unhealthy occupation, and gave figures from the London Hospital experience. The pamphlet complained of the atmosphere of servility amongst nurses, exemplified by the rule that nurses were required to remain standing when a member of the staff was present. The writer of the pamphlet was surely confusing servility with Civility. If Mr. Ramsay MacDonald came into the room at that moment he (the speaker) would stand up as a mark of respect to a man who was by reason of his position for the time being his superior. It was said that there was naturally a bias on the part of the management of hospitals to give preference in admissions to those who could pay, and that it was difficult for the administrative and nursing staff not to show a difference in the case of paying patients. But the patients were admitted to most hospitals, not by the management at all, but by the doctor in the receiving room, who decided whether the case was or was not a fit one for admission. He had always found in life that the man who attributed motives to another attributed those motives which would have actuated himself in like circumstances. When this writer said that those who could pay were naturally preferred he was indicating what he (the writer) would do. No man could have made such a statement who had spent a healthy moment in a voluntary hospital. The pamphlet stated that there was a reluctance on the part of patients to enter a hospital owing to the widespread feeling that they would be made the subjects of experimental treatment. There would be no such feeling in a State hospital, of course, because there would be no fear of sufficient provision by the State of research institutes ! But what about this widespread reluctance when 125,000 people came to the London Hospital alone last year? What about the feeling among our fellow citizens that their only chance of recovery was at the voluntary hospitals? What about this long waiting list of people anxious to be experimented on? There was not a word of all this in tlie pamphlet, but publicity was given to the ignorant and hysterical chatter of some charwomen, and that was thought worthy of the Labour party and the trade union organizations. At the conclusion of his address Lord Knutsford put forward his own scheme for the strengthening of the voluntary hospitals so as to make them capable of affording the best institutional treatment to all who needed it. He would divide the whole country up into districts, and in each district he would combine under one management all the voluntary hospitals. He would also take away from the Guardians all the Poor Law infirmaries and attach them as annexes to the mother hospital. The Minister of Health would make large grants to the mother hospital, and therefore he must be given power to nominate on to its management representatives of the State and of the district served. This would secure State control without State management. State control would satisfy most taxpayers — not all — but State management would satisfy nobody. It should be the object of such an institution to help — not to harm — the general practitioners of the neighbourhood. The hospital work must be regarded as, and must in fact be, supplementary to the work of the general practitioners. The financial part of the scheme he would not elaborate, but it would include a method whereby every individual, by the time he or she reached the age of 25 — an age of considerable earning capacity and the minimum of family responsibility — would have made a payment of £10. In addition to this he would have something corresponding to the scheme of the Hospital Saving Association, and he would also make every effort to keep voluntary subscriptions up to a high level. Lord Knutsford, notwithstanding his pungent criticisms of the pamphlet, was given a round of general applause when he sat down. Lord Somerleyton, who represented King Edward's Hospital Fund, said that so far as London was concerned the voluntary system was not at all likely to disappear. The position of the voluntary hospitals had improved in recent years and was still improving. But if an institution were put on the rates it would mean the end of voluntary help so far as that institution was concerned. He was of opinion also, in spite of all that was said about servility and red tape in a voluntary institution, that these things would flourish even more in an institution which was on the rates. Finally he gave some figures showing the recent and present position. In 1920 the deficit on the total funds of the London voluntary hospitals was £383,000; in 1921 it was £210,000; in 1922 it had fallen further to £174,000. For 1923 the figures could only be at present estimated, but they appeared to show a surplus of something like £200,000. This was due to some large legacies which had been received by two or three hospitals, but even omitting these windfalls any deficit would certainly not be more than £25,000. This improvement in the funds of the London hospitals was not due to desperate and spasmodic efforts, but was the result of steady effort, which was placing these institutions on a sound footing. Sir Alan Anderson, speaking as one of the honorary secretaries of King Edward's Fund, described the Labour party pamphlet as intelligent but inhuman. It dealt with men and women as if they were putty, whereas in fact the British man or woman had a very strong individuality. The remedies put forward in this pamphlet reminded him of the doctor who was called in to treat a child for whooping-cough, and when a fellow practitioner expressed astonishment at his prescription, said, "Well, you see, I am no good at whooping-cough, but this will give the little beggar fits, and I am a stunner at fits." He admitted that there were defects in the present hospital system. All of them were living more or less in a mirage due to their inability to realize the silent revolution which had taken place in this country whereby the old division between rich and poor had largely ceased to exist. He described the working of certain contributory schemes for workmen of which he had cognizance as the director of a railway company. At Derby 98 per cent. of the men in some of the big engineering shops were paying into such a fund. Even in London, after a year's work, the hospitals had an income of £30,000 from this source, and during the same year 6,700 contributors had been treated under this scheme. His own view was that finance was not the real difficulty of the hospital question. The economics of the question as it affected the medical profession had to be studied just as carefully as the economics of the hospital public. On this matter a final satisfactory conclusion had not yet been reached, but he thought it would be forthcoming. Mr. E. Corbey (National Association of Trade Union Approved Societies) thought they were regarding the problem too much as a London problem, and were ignoring the conditions in other parts of the country. He declared that he had had to send some of his members to certain medical men and pay a fee because he knew that was the only way to get them into the local hospitals. However much Lord Knutsford had criticized the pamphlet, his conclusions and the recommendations in the pamphlet appeared to be identical. Dr. F. E. Fremantle, M.P., thought that those who approached the matter from the State point of view and those who approached it from the voluntary hospital point of view got into the same difficulties because they took as the basis of their argument the complicated position which existed in the large industrial areas. They would do better to consider the position in the more rural communities, where treatment and preventive work were not dissevered. The large general hospitals should not occupy their thoughts too much, but rather the small cottage hospitals which were linked up with a general practitioner and nursing service. The Labour party was always trying to separate prevention and treatment — (" No ") — it was always calling for more whole-time officers and fewer part-time officers, and trying to distinguish and specialize. He thought that the line which hospital development might well take was the line which had been taken in education during the last fifty years, where a voluntary system had existed side by side with a State system. There was no reason why the two systems — voluntary and State - should not work together, the one making up for the deficiencies of the other, and so making possible a complete provision. Mr. G. W. Canter (Labour Party Advisory Committee) said they were all agreed that the existing hospital accommodation was totally inadequate. The Labour party had put forward certain proposals to meet the situation; he had not yet heard any contradiction of the argument underlying those proposals. No one objected to the proposal to lift the Poor Law medical service out of the Poor Law, or to utilize the great Poor Law hospitals as general hospitals. (Lord Knutsford : I do.) He himself regarded Lord Knutsford's own scheme as an endorsement of the Labour party's 36/L41/1/8